The Indonesian Economy in the Nineteenth and Twentieth Centuries - Booth, A. author. aut Link
XVI, 377 p.
Keywords: Indonesia is now the fourth largest country in the world, but many aspects of its economic history remain poorly understood. This book is the first comprehensive survey of Indonesian economic history in the 19th and 20th centuries, examining both the Dutch colonial era, and the post-independence period. Extensive use is made of recent work by Dutch, Indonesian and Australian scholars to develop a number of key themes relating to economic growth and structural transformation of the Indonesian economy from the early 19th century to the present.